2002
DOI: 10.1159/000058012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type-2 Diabetes in Patients with Hepatitis C and B Virus Infection in Jeddah, Saudi Arabia

Abstract: Objectives: To determine the prevalence of type-2 diabetes mellitus (DM) in patients with hepatitis C virus (HCV) and B virus (HBV) infections. Materials and Methods: A cross-sectional study of HCV- and HBV-positive patients admitted to King Abdul Aziz University Hospital, Jeddah, Saudi Arabia, was conducted from January 1999 to September 2000. The following data were collected and analysed: demographic data, the presence and type of DM, details of the treatment, body mass index (BMI), family history of DM, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The probable role could be due to induction of insulin resistance through destruction of insulin signaling pathways associated with overproduction of proinflammatory cytokines, such as IL-6 and TNF-α, in response to HCV infection and direct and/or indirect immune-mediated cytopathic effects of HCV on pancreatic islet cells, which may result in the destruction of β-cells and subsequently reduced insulin production [4, 21-23]. Insulin resistance presents at the early stages of chronic HCV infectioin, even prior to progression to fibrosis and cirrhosis [21, 22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable role could be due to induction of insulin resistance through destruction of insulin signaling pathways associated with overproduction of proinflammatory cytokines, such as IL-6 and TNF-α, in response to HCV infection and direct and/or indirect immune-mediated cytopathic effects of HCV on pancreatic islet cells, which may result in the destruction of β-cells and subsequently reduced insulin production [4, 21-23]. Insulin resistance presents at the early stages of chronic HCV infectioin, even prior to progression to fibrosis and cirrhosis [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Laloo et al [28] and Akbar et al [23] demonstrated that HCV seropositivity among diabetic patients is associated with raised ALT and AST levels. This discrepancy between our results and those of previous studies might be due to some differences in the duration of diabetes, type of treatment, severity of liver diseases, and level of liver enzymes among diabetic patients in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of DM in HCV patients is not exclusively related to cirrhosis. Non-cirrhotic patients with chronic HCV have increased prevalence of type-2 DM compared to non-cirrhotic patients with chronic hepatitis B virus [Akbar et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to 22% prevalence of DM-2 in patients with HCV infection reported earlier from the KSA. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[12–14] However, data from KSA on the factors influencing the occurrence of DM-2 in patients with liver disease are scanty. [15] We carried out this retrospective study with the aim of (a) determining the prevalence of DM-2 in patients with liver disease in KSA and (b) studying and analyzing various factors that could possibly affect the occurrence of DM-2 in patients with liver disease.…”
mentioning
confidence: 99%